Develop a B2C E-commerce strategy for the Forest Land Company to improve sales performance - Nguyen, Vu Kim Trang (H. : ĐHQGHN, 2020)
From the necessary of e-commerce, development or architectural and interior market, status-quo of forest land, the author point out some implications in order to improve the business performance and enhance the commerce activities of Forest Land Company.